A tubular lead-carbon storage battery positive grid and a preparation method thereof
Patent Information
- Application Number
- CN202611133155.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]针对目前管式蓄电池正极板的问题涉及活性物质的脱落、板栅的变形、腐蚀断裂等问题,本发明提供一种管式铅炭蓄电池正极板栅及其制备方法,与传统的含铅芯的铅酸蓄电池正极板栅相比,本发明正极板栅抗拉强度可提高20%以上,电池循环寿命提高30%以上,正极板导电性好,电池充电接受能力提高20%以上
(1)本发明采用的集成化压铸铝芯复合管状板栅,标志着一种从传统铅基合金向高导电轻量化复合材料体系的结构演变。该板栅通过一体化压铸工艺将铝芯导电梁与带有定位铆钉的筋条高效集成,利用铝材优异的电子传导特性,彻底规避了传统铅钙合金因“无锑效应”引发的早期容量衰减及充电接受能力严重受限的技术瓶颈;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a positive electrode grid of a tubular lead-carbon battery and its preparation method, belonging to the field of lead-acid battery technology. Background Technology
[0002] The traction battery uses tubular electrode plates, which include a tubular grid and lead paste. The tubular grid includes an upper frame with tabs and a lead core (vertical rib) on one side of the upper frame. When the tubular grid is made into a tubular electrode plate, a sleeve is fitted onto the lead core, and lead paste is poured into the gap between the sleeve and the lead core. The bottom end of the sleeve is sealed with a bottom buckle. When the electrode plate widths are equal, the length of the lead core determines the electrode plate capacity. Patent CN202487700U discloses a battery electrode plate, specifically a braided tubular sealed lead-acid power battery anode plate, including tabs. A comb-shaped grid is die-cast below the tabs. The grid consists of an ABS plastic grid frame and a pure lead wire woven mesh, wherein the pure lead wire woven mesh is woven and wrapped around the surface of the ABS plastic grid frame. However, the ABS plastic plate has poor conductivity, which is a drawback.
[0003] Currently, the problems with the positive plates of tubular lead-acid batteries involve multiple aspects, including active material shedding, grid deformation, corrosion and fracture, plate sulfation, and the influence of impurities. The grids of tubular lead-acid batteries are made of two different multi-element alloys: a lead-antimony alloy and a lead-calcium alloy. Due to the presence of antimony, the lead-antimony alloy accelerates battery self-discharge and lowers the hydrogen evolution potential, accelerating the decomposition and loss of water in the electrolyte. Therefore, the lead-antimony alloy is mainly used to manufacture flooded lead-acid batteries. Flooded batteries produce acid mist during charging, causing environmental pollution. With increasingly stringent national environmental protection requirements, the demand for valve-regulated maintenance-free batteries is becoming more urgent. Valve-regulated maintenance-free batteries generally use a lead-calcium alloy, which effectively suppresses battery self-discharge and water decomposition, has higher conductivity, and significantly improves the mechanical strength of the grid. Although the lead-calcium alloy can meet many performance requirements of sealed valve-regulated batteries, it is prone to premature capacity decay due to the "antimony-free effect." Conventional tubular positive electrode grids have lead cores with circular, elliptical, rectangular, or staggered semicircular cross-sections. To improve the corrosion resistance of the lead core, the grid is die-cast, resulting in high density and a very smooth surface. Therefore, in grids manufactured using the conventional lead core shape and die-casting process, during battery discharge, the lead sulfate converted from the positive electrode active material spreads along this continuous, smooth metal surface, forming a dense insulating film. This blocks the conductive channels between the grid and the active material, weakens the connection between the active material and the grid, exacerbates the early capacity decay caused by the "antimony-free effect," reduces charge acceptance, and significantly shortens the battery's cycle life.
[0004] Therefore, there is an urgent need to develop tubular lead-carbon battery positive electrode grids with good conductivity, high strength, and high charge / discharge acceptance. Summary of the Invention
[0005] To address the current problems with the positive plate of tubular batteries, such as active material shedding, grid deformation, and corrosion fracture, this invention provides a tubular lead-carbon battery positive plate grid and its preparation method. Compared with the traditional lead-core lead-acid battery positive plate grid, the positive plate grid of this invention can increase the tensile strength by more than 20%, increase the battery cycle life by more than 30%, improve the conductivity of the positive plate, and increase the battery charge acceptance by more than 20%.
[0006] A tubular lead-carbon battery positive electrode grid includes tabs 1, conductive beams 2, polyester braided sleeves 3, sleeve plugs 4, and aluminum-based lead alloy composite rods 5. Tabs 1 are provided at the top of the conductive beams 2, and aluminum-based lead alloy composite rods 5 are vertically arranged at equal intervals at the bottom of the conductive beams 2. Polyester braided sleeves 3 are sleeved on the outside of the aluminum-based lead alloy composite rods 5, and the gap between the aluminum-based lead alloy composite rods 5 and the inner wall of the polyester braided sleeves 3 is filled with positive electrode active lead paste 6. The sleeve plugs 4 are provided at the bottom of the polyester braided sleeves 3. Several pairs of positioning elements 9 are provided on the side of the aluminum-based lead alloy composite rods 5 along the axial direction. The top of the aluminum-based lead alloy composite rods 5 is a conical structure 7, and the bottom of the conical structure 7 is an integrally formed elliptical composite rod structure 8. The electrode 1 comprises, from the inside out, an aluminum alloy layer I11, a brass layer I12, a lead-antimony-neodymium alloy layer I13, and a lead-tin-bismuth alloy layer I14; The conductive crossbeam 2 comprises, from the inside out, an aluminum alloy layer II21, a brass layer II22, a lead-antimony-neodymium alloy layer II23, and a lead-tin-bismuth alloy layer II24; The aluminum-based lead alloy composite rod 5 comprises, from the inside out, an aluminum alloy layer Ⅲ51, a brass layer Ⅲ52, a lead-antimony-neodymium alloy layer Ⅲ53, a lead-tin-bismuth alloy layer Ⅲ54, and a lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide.
[0007] Preferably, the positioning element 9 includes positioning element I 91 and positioning element II 92. Positioning element I 91 and positioning element II 92 are alternately arranged along the axial direction on the outside of the elliptical composite rod structure 8. Each pair of positioning elements I 91 is arranged along the major axis of the elliptical composite rod structure 8 and is symmetrical with respect to the central axis of the aluminum-based lead alloy composite rod 5. Each pair of positioning elements II 92 is arranged along the minor axis of the elliptical composite rod structure 8 and is symmetrical with respect to the central axis of the aluminum-based lead alloy composite rod 5. The spacing between adjacent pairs of positioning elements I 91 is equal, and the spacing between adjacent pairs of positioning elements II 92 is equal.
[0008] Preferably, the tab 1 is a cuboid structure with a height of 20-50mm, a width of 10-40mm, and a thickness of 5-10mm; the conductive beam 2 has parallel upper and lower sides, with an upper side length of 10-40mm, a lower side length of 160-480mm, and a thickness of 5-10mm; the polyester braided sleeve 3 has a length of 180-1000mm, a width of 160-480mm, and an inner diameter of 5-10mm; the conical structure 7 has an upper base cross-section diameter of 5-10mm and a lower base cross-section diameter of 2-6mm; the elliptical composite rod 8 has a major axis length of 2.5-7.0mm and a minor axis length of 2.0-5.0mm; and the single positioning element 9 has a cross-sectional length of 0.1-1.0mm and a width of 0.05-0.5mm.
[0009] Preferably, the thickness of brass layer I12 is 5~30µm, and the thicknesses of brass layer I12, brass layer II22, and brass layer III52 are the same; the thickness of lead-antimony-neodymium alloy layer I13 is 20~100µm, and the thicknesses of lead-antimony-neodymium alloy layer I13, lead-antimony-neodymium alloy layer II23, and lead-antimony-neodymium alloy layer III53 are the same; the thickness of lead-tin-bismuth alloy layer I14 is 0.5~2.0mm, and the thicknesses of lead-tin-bismuth alloy layer I14, lead-tin-bismuth alloy layer II24, and lead-tin-bismuth alloy layer III54 are the same; and the thickness of the lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide is 0.2~1.0mm.
[0010] By mass percentage, the aluminum alloy contains 0.01~0.5% Ca, 0.5~2.0% Mn, 0.01~0.1% Ce, and 0.05~1.2% Zr, with the balance being Al; by mass percentage, the lead-antimony-neodymium alloy layer contains 0.5~2.0% Sb and 0.001~0.2% Nd, with the balance being Pb; by mass percentage, the lead-tin-bismuth alloy layer contains 0.5~2.0% Sn and 0.05~0.5% Bi, with the balance being Pb; by mass percentage, the lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide contains 1.0~5.0% B4C, 0.5~2.0% CeO2, and 0.5~2.0% Sn, with the balance being Pb.
[0011] By mass percentage, the positive electrode active lead paste 6 contains 3.0-10.0% Pb3O4, 0.05-0.20% stannous sulfate, 0.10-0.50% graphite powder, 0.05-0.15% short fibers, 0.10-0.40% tetrabasic lead sulfate, 0.10-0.50% conductive fibers, 7.0-11.0% concentrated sulfuric acid, 5.0-12.0% H2O, 0.05-0.50% bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material, and the balance is lead-tin alloy powder containing 0.1 wt.% Sn.
[0012] More preferably, the preparation method of the bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI) in the positive electrode active lead paste specifically includes: 1) Dissolve zinc nitrate and bismuth nitrate in anhydrous methanol solution to form a metal salt solution; the molar ratio of zinc nitrate to bismuth nitrate is 9~15:1; 2) Under vigorous stirring, a methanol ligand solution containing 2-methylimidazole was added dropwise to the metal salt solution. The reaction was stirred at room temperature for 24-48 hours to complete the self-assembly. After centrifugation, the mixture was washed multiple times with anhydrous ethanol and dried under vacuum to obtain the Bi-ZIF-8 precursor (MOF). The total molar ratio of zinc ions and bismuth ions in the metal salt solution to 2-methylimidazole (C4H6N2) was 1:4-8. 3) The Bi-ZIF-8 precursor was placed in a tube furnace and heated to 800-1000℃ for high-temperature pyrolysis for 3-6 hours under an argon or nitrogen atmosphere at a heating rate of 5-20℃ / min. After cooling to room temperature in the furnace, excess elemental zinc was removed by washing with dilute hydrochloric acid to obtain bismuth-doped porous carbon (Bi-MOF-C) with a high specific surface area. The concentration of the hydrochloric acid was 2-5 mol / L. 4) Bismuth-doped porous carbon (Bi-MOF-C) was uniformly dispersed in hydrochloric acid solution. Aniline monomer and initiator ammonium persulfate (APS) were added sequentially under stirring at a temperature of 0-5℃ and the reaction was carried out in situ for oxidative polymerization for 12-24 h. After washing with deionized water until neutral, the mixture was vacuum dried for 24-48 h to obtain a bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI). The concentration of the hydrochloric acid solution was 1-3 mol / L, the mass ratio of bismuth-doped porous carbon (Bi-MOF-C) to aniline monomer was 1:1-3, and the molar ratio of aniline monomer to initiator ammonium persulfate (APS) was 1:1-1:3.
[0013] The method for preparing the positive electrode grid of the tubular lead-carbon battery includes the following steps: S1. Preparation of aluminum alloy grid substrate: Molten aluminum alloy liquid is injected into a positive electrode grid mold for die casting, cooled, and finely repaired. Then, it is subjected to degreasing and surface sandblasting treatment in sequence to obtain aluminum alloy grid substrate; the aluminum alloy grid substrate includes aluminum alloy I for the tabs, aluminum alloy II for the conductive beams, and aluminum alloy III for the aluminum-based lead alloy composite rods. S2. Preparation of the brass layer: The aluminum alloy grid substrate is immersed in a primary zinc plating solution for primary immersion plating. After cleaning with deionized water, it is activated in an HNO3 solution and then immersed in a secondary zinc plating solution for secondary immersion plating. After cleaning with deionized water, a zinc@aluminum alloy substrate is obtained. Using the zinc@aluminum alloy substrate as the cathode and the Zn-Cu alloy as the anode, constant current electrodeposition is performed in a copper electroplating solution. After cleaning with deionized water and drying, an aluminum alloy grid substrate coated with a brass layer is obtained. The brass layer includes brass layer I, brass layer II, and brass layer III. S3. Preparation of lead-antimony-neodymium alloy layer: The aluminum alloy grid substrate coated with brass layer is immersed in flux activation solution for activation, then immersed in lead-antimony-neodymium alloy melt for plating treatment, and immediately cooled in anhydrous ethanol to obtain an aluminum alloy grid substrate coated with lead-antimony-neodymium alloy layer; the lead-antimony-neodymium alloy layer includes lead-antimony-neodymium alloy layer I, lead-antimony-neodymium alloy layer II and lead-antimony-neodymium alloy layer III; S4. Preparation of lead-tin-bismuth alloy layer: An aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer and a brass layer is placed in a mold, and molten lead-tin-bismuth alloy is injected into the mold for die casting. After cooling and finishing, an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is obtained. The lead-tin-bismuth alloy layer includes lead-tin-bismuth alloy layer I, lead-tin-bismuth alloy layer II, and lead-tin-bismuth alloy layer III. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer I is the electrode tab, and the aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer II is the conductive beam. S5. Preparation of lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide: The bottom of an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is inserted into the hole of a titanium strip to form an integral grid. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer III is used as the cathode, and the Pb-2%Sn alloy plate is used as the anode. Constant current electrodeposition is performed in an alkaline lead plating solution. After washing with deionized water and drying, the titanium strip is removed to obtain an aluminum alloy grid substrate coated with a lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide. The aluminum alloy grid substrate coated with the lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide is an aluminum-based lead alloy composite rod. S6. Insert the aluminum alloy grid substrate with a lead-tin composite coating of nano-boron carbide / nano-cerium dioxide into a polyester braided sleeve, then invert it so that the conductive beam is at the bottom, fill the gap between the aluminum-based lead alloy composite rod and the inner wall of the polyester braided sleeve with positive electrode active lead paste, seal the positive electrode active lead paste in the polyester braided sleeve with a sleeve plug, and suspend it for 24 hours to obtain the positive electrode grid of the tubular lead-carbon battery.
[0014] Preferably, the method for preparing the molten aluminum alloy in step S1 is as follows: pure aluminum, Al-20%Mn master alloy, Al-5%Ce master alloy, and Al-5%Zr master alloy are added to a melting furnace, heated to 660~720℃ and held at that temperature to melt, and stirred by electromagnetic field for 5~20 minutes to obtain an aluminum alloy melt. Then, a refining agent is added for refining, and the molten aluminum alloy is obtained after slag removal. More preferably, by mass percentage, the refining agent contains 25~50% NaCl, 30~40% KCl, 15~25% MgCl2, and 5~10% hexachloroethane (C2Cl6); the refining agent accounts for 0.5~2.0 wt% of the aluminum alloy melt. The preparation method of the lead-antimony-neodymium alloy melt in step S3 is as follows: pure lead, pure antimony, and lead-2% neodymium master alloy are added to a melting furnace, heated to 400~600℃ and held for melting, and stirred with an electromagnetic field for 5~20 minutes to obtain molten lead alloy. Ammonium chloride powder is added as a purifying agent for stirring and purification, and the slag is removed after settling to obtain the lead-antimony-neodymium alloy melt; more preferably, the amount of ammonium chloride powder added is 0.5~2.0 wt% of the molten lead alloy. The preparation method of lead-tin-bismuth alloy melt in step S4 is as follows: pure lead, pure tin and pure bismuth are added to a melting furnace, heated to 300~400℃ and held for melting, and stirred by electromagnetic field for 5~20min to obtain alloy melt. Ammonium chloride powder is added as a purifying agent and stirred for purification. After standing and removing slag, lead-tin-bismuth alloy melt is obtained. More preferably, the amount of ammonium chloride powder added is 0.5~2.0wt% of the alloy melt.
[0015] Preferably, in step S2, the mass concentration of the HNO3 solution is 10-40%, and the activation time is 1-10 seconds. The zinc plating solution in step S2 contains 50-70 g / L ZnO, 250-350 g / L NaOH, 1-2 g / L FeCl3·6H2O, and 10-30 g / L potassium sodium tartrate; the zinc plating solution in the second immersion contains 20-40 g / L ZnO, 100-200 g / L NaOH, 1-2 g / L FeCl3·6H2O, 30-60 g / L potassium sodium tartrate, and 0.5-2 g / L NaNO3. The copper electroplating solution in step S2 contains 20-40 g / L copper pyrophosphate, 10-30 g / L zinc pyrophosphate, and 40-80 g / L potassium pyrophosphate, with a pH value of 9.0-11.0. The flux activating solution in step S3 contains 40-80 wt% rosin, 10-40 wt% n-butanol, 2-6 wt% succinic acid, 0.1-0.5 wt% fatty acid polyoxyethylene ether, 0.1-0.2 wt% hydroquinone and 7.8-13.3 wt% anhydrous ethanol; The alkaline lead plating solution in step S5 contains 10~50g / L lead oxide, 10~30g / L potassium hydroxide, 5~20g / L potassium stannate, 30~80g / L sodium potassium tartrate, 5~20g / L nano B4C, and 5~20g / L nano CeO2.
[0016] Preferably, the pressure for die casting in step S1 is 50~200 bar; In step S2, the temperature for the first immersion plating is 10~25℃, and the time is 30~60s; the temperature for the second immersion plating is 10~25℃, and the time is 10~30s; the cathode current density for constant current electrodeposition is 0.5~3A / dm³. 2 The temperature is 50~70℃, and the time is 5~30min; The immersion activation temperature in step S3 is 100~200℃, and the immersion activation time is 10~60S; the immersion plating time is 20~120S. The pressure for die casting in step S4 is 90~180 bar; The cathode current density for constant current electrodeposition in step S5 is 0.5~3 A / dm². 2 The temperature is 20~50℃, and the time is 1~6h.
[0017] The beneficial effects of this invention are: (1) The integrated die-cast aluminum core composite tubular grid used in this invention marks a structural evolution from traditional lead-based alloys to a highly conductive and lightweight composite material system. The grid efficiently integrates the aluminum core conductive beam with the ribs with positioning rivets through an integrated die-casting process. By utilizing the excellent electronic conductivity of aluminum, it completely avoids the technical bottleneck of early capacity decay and severely limited charge acceptance caused by the "antimony-free effect" in traditional lead-calcium alloys. (2) At the interface engineering level, the aluminum core surface is subjected to sandblasting, alkaline washing and degreasing and multi-layer composite coating process (in sequence, zinc-plated brass layer, hot-dip lead-antimony-neodymium alloy layer and electrodeposited lead alloy protective layer, etc.), which builds a tight electrochemical anti-corrosion barrier and ensures the long-term thermodynamic stability of the skeleton in a strong acid environment. (3) The radial physical constraint system formed by the high-strength polyester nonwoven tubing in this invention locks the positive electrode active material tightly in the "constant pressure cavity", effectively offsetting the phase change stress generated during cycling and preventing the softening and shedding of the active material. This aluminum core composite structure not only significantly improves the specific power density of the battery, but also gives the battery long-term reliability through the organic unity of multi-layer interface coupling effect and tubular physical constraint; (4) The stannous sulfate and bismuth doping components of this invention have a synergistic regulatory effect on the interfacial reaction, which can increase the oxygen evolution overpotential, suppress the occurrence of side reactions, thereby reducing water loss and improving cycle stability; the structural induction effect of 4BS seed crystals and MOF-derived porous carbon helps to form a stable and dense cathode solidification structure, improves ion transport channels and enhances reaction reversibility. At the same time, the reinforcing support effect of short fibers and the interfacial bonding effect of conductive polymers jointly improve the mechanical strength and anti-softening ability of active materials; under the combined effect, the cathode system of this invention exhibits higher structural stability, lower polarization and better cycle life and rate performance under deep cycling conditions; (5) The present invention uses nano B4C and nano CeO2 lead-tin composite coating, which is beneficial to improve the corrosion resistance of the positive electrode grid and increase the oxygen evolution overpotential, so that the positive electrode will not generate a large number of bubbles during long-term use and reduce the volatilization of acid mist moisture. (6) This invention uses Bi-MOF-C@PANI material, which introduces bismuth element through MOF precursor, forms a porous carbon framework through high-temperature carbonization, and then polymerizes conductive polymer in situ on its surface. This system constructs a multi-scale conductive network composed of colloidal graphite, conductive fibers and nanocomposite materials inside the positive electrode, which effectively improves the continuity of electron transport and reduces internal resistance, while significantly improving the utilization efficiency of active materials; (7) The preparation method of this invention utilizes the spatial confinement effect of ZIF-8 to achieve uniform dispersion of Bi elements at the atomic level. The Bi-MOF-C formed by high-temperature pyrolysis has a high specific surface area and abundant mesoporous structure, which is beneficial to electrolyte wetting and rapid ion transport. Finally, the polyaniline (PANI) coated by in-situ polymerization not only provides additional electron transport channels, but also protects the internal carbon skeleton from premature oxidation in the strongly oxidizing cathode environment. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the positive electrode grid of a tubular lead-carbon battery. Figure 2 This is a front view of the positive electrode grid of a tubular lead-carbon battery. Figure 3 A picture showing the details of the positive plate grid of a tubular lead-carbon battery; Figure 4 Two images showing the details of the positive plate grid of a tubular lead-carbon battery; Figure 5 for Figure 2 A schematic diagram of the AA cross-section; Figure 6 for Figure 2 BB cross-sectional diagram; Figure 7 for Figure 2 A schematic diagram of the CC cross-section; Figure 8 for Figure 2 DD cross-sectional schematic diagram; Figure 9 Schematic diagram of polyester braided sleeve; Figure 10 This is a schematic diagram of a sleeve plug; In the diagram: 1-Electrode tab, 11-Aluminum alloy I, 12-Brass layer I, 13-Lead-antimony-neodymium alloy layer I, 14-Lead-tin-bismuth alloy layer I, 2-Conductive crossbeam, 21-Aluminum alloy II, 22-Brass layer II, 23-Lead-antimony-neodymium alloy layer II, 24-Lead-tin-bismuth alloy layer II, 3-Polyester braided sleeve, 4-Sleeve plug, 5-Aluminum-based lead alloy composite rod, 51-Aluminum alloy III, 52-Brass layer III, 53-Lead-antimony-neodymium alloy layer III, 54-Lead-tin-bismuth alloy layer III, 55-Lead-tin composite plating layer doped with nano-boron carbide / nano-cerium dioxide, 6-Positive electrode active lead paste, 7-Conical structure, 8-Elliptical composite rod structure, 9-Positioning component, 91-Positioning component I, 92-Positioning component II. Detailed Implementation
[0019] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the content described. Invention Overview A tubular lead-carbon battery positive electrode grid includes tabs 1, conductive beams 2, polyester braided sleeves 3, sleeve plugs 4, and aluminum-based lead alloy composite rods 5. Tabs 1 are provided at the top of the conductive beams 2, and aluminum-based lead alloy composite rods 5 are vertically arranged at equal intervals at the bottom of the conductive beams 2. Polyester braided sleeves 3 are sleeved on the outside of the aluminum-based lead alloy composite rods 5, and the gap between the aluminum-based lead alloy composite rods 5 and the inner wall of the polyester braided sleeves 3 is filled with positive electrode active lead paste 6. The sleeve plugs 4 are provided at the bottom of the polyester braided sleeves 3. Several pairs of positioning elements 9 are provided on the side of the aluminum-based lead alloy composite rods 5 along the axial direction. The top of the aluminum-based lead alloy composite rods 5 is a conical structure 7, and the bottom of the conical structure 7 is an integrally formed elliptical composite rod structure 8. The electrode 1 comprises, from the inside out, an aluminum alloy layer I11, a brass layer I12, a lead-antimony-neodymium alloy layer I13, and a lead-tin-bismuth alloy layer I14; The conductive crossbeam 2 comprises, from the inside out, an aluminum alloy layer II21, a brass layer II22, a lead-antimony-neodymium alloy layer II23, and a lead-tin-bismuth alloy layer II24; The aluminum-based lead alloy composite rod 5 comprises, from the inside out, an aluminum alloy layer Ⅲ51, a brass layer Ⅲ52, a lead-antimony-neodymium alloy layer Ⅲ53, a lead-tin-bismuth alloy layer Ⅲ54, and a lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide.
[0021] Preferably, the positioning element 9 includes positioning element I 91 and positioning element II 92. Positioning element I 91 and positioning element II 92 are alternately arranged along the axial direction on the outside of the elliptical composite rod structure 8. Each pair of positioning elements I 91 is arranged along the major axis of the elliptical composite rod structure 8 and is symmetrical with respect to the central axis of the aluminum-based lead alloy composite rod 5. Each pair of positioning elements II 92 is arranged along the minor axis of the elliptical composite rod structure 8 and is symmetrical with respect to the central axis of the aluminum-based lead alloy composite rod 5. The spacing between adjacent pairs of positioning elements I 91 is equal, and the spacing between adjacent pairs of positioning elements II 92 is equal.
[0022] Preferably, the tab 1 is a cuboid structure with a height of 20-50mm, a width of 10-40mm, and a thickness of 5-10mm; the conductive beam 2 has parallel upper and lower sides, with an upper side length of 10-40mm, a lower side length of 160-480mm, and a thickness of 5-10mm; the polyester braided sleeve 3 has a length of 180-1000mm, a width of 160-480mm, and an inner diameter of 5-10mm; the conical structure 7 has an upper base cross-section diameter of 5-10mm and a lower base cross-section diameter of 2-6mm; the elliptical composite rod 8 has a major axis length of 2.5-7.0mm and a minor axis length of 2.0-5.0mm; and the single positioning element 9 has a cross-sectional length of 0.1-1.0mm and a width of 0.05-0.5mm.
[0023] Preferably, the thickness of brass layer I12 is 5~30µm, and the thicknesses of brass layer I12, brass layer II22, and brass layer III52 are the same; the thickness of lead-antimony-neodymium alloy layer I13 is 20~100µm, and the thicknesses of lead-antimony-neodymium alloy layer I13, lead-antimony-neodymium alloy layer II23, and lead-antimony-neodymium alloy layer III53 are the same; the thickness of lead-tin-bismuth alloy layer I14 is 0.5~2.0mm, and the thicknesses of lead-tin-bismuth alloy layer I14, lead-tin-bismuth alloy layer II24, and lead-tin-bismuth alloy layer III54 are the same; and the thickness of the lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide is 0.2~1.0mm.
[0024] By mass percentage, the aluminum alloy contains 0.01~0.5% Ca, 0.5~2.0% Mn, 0.01~0.1% Ce, and 0.05~1.2% Zr, with the balance being Al; by mass percentage, the lead-antimony-neodymium alloy layer contains 0.5~2.0% Sb and 0.001~0.2% Nd, with the balance being Pb; by mass percentage, the lead-tin-bismuth alloy layer contains 0.5~2.0% Sn and 0.05~0.5% Bi, with the balance being Pb; by mass percentage, the lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide contains 1.0~5.0% B4C, 0.5~2.0% CeO2, and 0.5~2.0% Sn, with the balance being Pb.
[0025] By mass percentage, the positive electrode active lead paste 6 contains 3.0-10.0% Pb3O4, 0.05-0.20% stannous sulfate, 0.10-0.50% graphite powder, 0.05-0.15% short fibers, 0.10-0.40% tetrabasic lead sulfate, 0.10-0.50% conductive fibers, 7.0-11.0% concentrated sulfuric acid, 5.0-12.0% H2O, 0.05-0.50% bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material, and the balance is lead-tin alloy powder containing 0.1 wt.% Sn.
[0026] The preparation method of the bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI) in the positive electrode active lead paste specifically includes: 1) Dissolve zinc nitrate and bismuth nitrate in anhydrous methanol solution to form a metal salt solution; the molar ratio of zinc nitrate to bismuth nitrate is 9~15:1; 2) Under vigorous stirring, a methanol ligand solution containing 2-methylimidazole was added dropwise to the metal salt solution. The reaction was stirred at room temperature for 24-48 hours to complete the self-assembly. After centrifugation, the mixture was washed multiple times with anhydrous ethanol and dried under vacuum to obtain the Bi-ZIF-8 precursor (MOF). The total molar ratio of zinc ions and bismuth ions in the metal salt solution to 2-methylimidazole (C4H6N2) was 1:4-8. 3) The Bi-ZIF-8 precursor was placed in a tube furnace and heated to 800-1000℃ for high-temperature pyrolysis for 3-6 hours under an argon or nitrogen atmosphere at a heating rate of 5-20℃ / min. After cooling to room temperature in the furnace, excess elemental zinc was removed by washing with dilute hydrochloric acid to obtain bismuth-doped porous carbon (Bi-MOF-C) with a high specific surface area. The concentration of the dilute hydrochloric acid was 2-4 mol / L. 4) Bismuth-doped porous carbon (Bi-MOF-C) was uniformly dispersed in hydrochloric acid solution. Aniline monomer and initiator ammonium persulfate (APS) were added sequentially under stirring at a temperature of 0-5℃ and the reaction was carried out in situ for oxidative polymerization for 12-24 h. After washing with deionized water until neutral, the mixture was vacuum dried for 24-48 h to obtain a bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI). The concentration of the hydrochloric acid solution was 1-3 mol / L, the mass ratio of bismuth-doped porous carbon (Bi-MOF-C) to aniline monomer was 1:1-3, and the molar ratio of aniline monomer to initiator ammonium persulfate (APS) was 1:1-1:3.
[0027] The method for preparing the positive electrode grid of the tubular lead-carbon battery includes the following steps: S1. Preparation of aluminum alloy grid substrate: Molten aluminum alloy liquid is injected into a positive electrode grid mold for die casting (the die casting pressure is 50~200 bar), cooled, finely trimmed, and then subjected to degreasing and surface sandblasting treatments to obtain the aluminum alloy grid substrate; the aluminum alloy grid substrate includes aluminum alloy I for the tabs, aluminum alloy II for the conductive beams, and aluminum alloy III for the aluminum-based lead alloy composite rods; the method for preparing the molten aluminum alloy liquid is as follows: pure aluminum, Al-20%Mn master alloy, Al-5%Ce master alloy, and A 1-5% Zr master alloy is added to a melting furnace, heated to 660-720℃ and held at that temperature until melted. The mixture is then stirred with an electromagnetic field for 5-20 minutes to obtain an aluminum alloy melt. A refining agent is then added for refining, and the slag is removed to obtain a molten aluminum alloy liquid. More preferably, by mass percentage, the refining agent comprises 25-50% NaCl, 30-40% KCl, 15-25% MgCl2, and 5-10% hexachloroethane (C2Cl6); the refining agent accounts for 0.5-2.0 wt% of the aluminum alloy melt. S2. Preparation of the brass layer: The aluminum alloy grid substrate is immersed in a primary zinc plating solution for primary immersion plating. After rinsing with deionized water, it is activated in an HNO3 solution and then immersed in a secondary zinc plating solution for secondary immersion plating. After rinsing with deionized water, a zinc@aluminum alloy substrate is obtained. Using the zinc@aluminum alloy substrate as the cathode and the Zn-Cu alloy as the anode, constant current electrodeposition is performed in a copper electroplating solution. After rinsing with deionized water and drying, an aluminum alloy grid substrate coated with a brass layer is obtained. The brass layer includes brass layer I, brass layer II, and brass layer III. The primary zinc plating solution contains 50~70 g / L ZnO, 250~350 g / L NaOH, and 1~2 g / L FeCl3·6H2O. The zinc plating solution contains 10-30 g / L potassium sodium tartrate; the primary immersion temperature is 10-25℃, and the time is 30-60 s; the secondary zinc plating solution contains 20-40 g / L ZnO, 100-200 g / L NaOH, 1-2 g / L FeCl3·6H2O, 30-60 g / L potassium sodium tartrate, and 0.5-2 g / L NaNO3; the secondary immersion temperature is 10-25℃, and the time is 10-30 s; the copper plating solution contains 20-40 g / L copper pyrophosphate, 10-30 g / L zinc pyrophosphate, and 40-80 g / L potassium pyrophosphate, with a pH of 9.0-11.0; the cathode current density for constant current electrodeposition is 0.5-3 A / dm³. 2 The temperature is 50~70℃, and the time is 5~30min; S3. Preparation of the lead-antimony-neodymium alloy layer: The aluminum alloy grid substrate coated with a brass layer is immersed in a flux activation solution for activation (immersion activation temperature is 100~200℃, immersion activation time is 10~60s), and then immersed in a lead-antimony-neodymium alloy melt for plating treatment (plating time is 20~120s), and immediately cooled in anhydrous ethanol to obtain an aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer; the lead-antimony-neodymium alloy layer includes lead-antimony-neodymium alloy layer I, lead-antimony-neodymium alloy layer II, and lead-antimony-neodymium alloy layer III; the flux activation solution contains 40~80wt% rosin and 10~40wt% n-butyl The alloy comprises: alcohol, 2-6 wt% succinic acid, 0.1-0.5 wt% fatty acid polyoxyethylene ether, 0.1-0.2 wt% hydroquinone, and 7.8-13.3 wt% anhydrous ethanol; the preparation method of the lead-antimony-neodymium alloy melt is as follows: pure lead, pure antimony, and lead-2% neodymium master alloy are added to a melting furnace, heated to 400-600℃ and held for melting, and stirred in an electromagnetic field for 5-20 minutes to obtain molten lead alloy. Ammonium chloride powder is added as a purifying agent for stirring and purification, and the mixture is allowed to stand and the slag is removed to obtain the lead-antimony-neodymium alloy melt; more preferably, the amount of ammonium chloride powder added is 0.5-2.0 wt% of the molten lead alloy. S4. Preparation of the lead-tin-bismuth alloy layer: An aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer and a brass layer is placed in a mold. Molten lead-tin-bismuth alloy is injected into the mold for die casting (the die casting pressure is 90~180 bar). After cooling and finishing, an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is obtained. The lead-tin-bismuth alloy layer includes lead-tin-bismuth alloy layer I, lead-tin-bismuth alloy layer II, and lead-tin-bismuth alloy layer III. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer I is a tab. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer II is a conductive crossbeam; the preparation method of the lead-tin-bismuth alloy melt is as follows: pure lead, pure tin, and pure bismuth are added to a melting furnace, heated to 300~400℃ and held for melting, and stirred by electromagnetic field for 5~20 minutes to obtain an alloy melt. Ammonium chloride powder is added as a purifying agent for stirring and purification, and the slag is removed after settling to obtain the lead-tin-bismuth alloy melt; more preferably, the amount of ammonium chloride powder added is 0.5~2.0 wt% of the alloy melt. S5. Preparation of lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide: The bottom of an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is inserted into the holes of a titanium strip to form an integral grid. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer III is used as the cathode, and the Pb-2%Sn alloy plate is used as the anode. Constant current electrodeposition is performed in an alkaline lead plating solution (the cathode current density for constant current electrodeposition is 0.5~3A / dm). 2The process involves washing with deionized water at a temperature of 20-50℃ for 1-6 hours, followed by drying. The titanium strip is then removed to obtain an aluminum alloy grid substrate coated with a lead-tin composite layer doped with nano-boron carbide / nano-cerium dioxide. The aluminum alloy grid substrate with the lead-tin composite layer doped with nano-boron carbide / nano-cerium dioxide is an aluminum-based lead alloy composite rod. The alkaline lead plating solution contains 10-50 g / L lead oxide, 10-30 g / L potassium hydroxide, 5-20 g / L potassium stannate, 30-80 g / L sodium potassium tartrate, 5-20 g / L nano-B4C, and 5-20 g / L nano-CeO2. S6. Insert the aluminum alloy grid substrate with a lead-tin composite coating of nano-boron carbide / nano-cerium dioxide into a polyester braided sleeve, then invert it so that the conductive beam is at the bottom, fill the gap between the aluminum-based lead alloy composite rod and the inner wall of the polyester braided sleeve with positive electrode active lead paste, seal the positive electrode active lead paste in the polyester braided sleeve with a sleeve plug, and suspend it for 24~48 hours to obtain the positive electrode grid of the tubular lead-carbon battery.
[0028] Example 1: A tubular lead-carbon battery positive electrode grid (see...) Figures 1-10 The device includes an electrode tab 1, a conductive beam 2, a polyester braided sleeve 3, a sleeve plug 4, and an aluminum-based lead alloy composite rod 5. The electrode tab 1 is set at the top of the conductive beam 2, and the aluminum-based lead alloy composite rod 5 is set vertically at equal intervals at the bottom of the conductive beam 2. The polyester braided sleeve 3 is sleeved on the outside of the aluminum-based lead alloy composite rod 5, and the gap between the aluminum-based lead alloy composite rod 5 and the inner wall of the polyester braided sleeve 3 is filled with positive electrode active lead paste 6. The sleeve plug 4 is set at the bottom of the polyester braided sleeve 3. Several pairs of positioning parts 9 are set along the axial direction on the side of the aluminum-based lead alloy composite rod 5. The top of the aluminum-based lead alloy composite rod 5 is a conical structure 7, and the bottom of the conical structure 7 is an integrally formed elliptical composite rod structure 8. The electrode tab 1 comprises, from the inside out, an aluminum alloy layer I11, a brass layer I12, a lead-antimony-neodymium alloy layer I13, and a lead-tin-bismuth alloy layer I14; The conductive crossbeam 2 comprises, from the inside out, an aluminum alloy layer II21, a brass layer II22, a lead-antimony-neodymium alloy layer II23, and a lead-tin-bismuth alloy layer II24; The aluminum-based lead alloy composite rod 5 comprises, from the inside out, an aluminum alloy layer Ⅲ51, a brass layer Ⅲ52, a lead-antimony-neodymium alloy layer Ⅲ53, a lead-tin-bismuth alloy layer Ⅲ54, and a lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide.
[0029] The positioning element 9 includes positioning element I 91 and positioning element II 92. Positioning element I 91 and positioning element II 92 are alternately arranged along the axial direction on the outside of the elliptical composite rod structure 8. Each pair of positioning elements I 91 is arranged along the major axis of the elliptical composite rod structure 8 and is symmetrical with respect to the central axis of the aluminum-based lead alloy composite rod 5. Each pair of positioning elements II 92 is arranged along the minor axis of the elliptical composite rod structure 8 and is symmetrical with respect to the central axis of the aluminum-based lead alloy composite rod 5. The spacing between adjacent pairs of positioning elements I 91 is equal, and the spacing between adjacent pairs of positioning elements II 92 is equal.
[0030] The electrode tab 1 is a cuboid structure with a height of 20mm, a width of 10mm, and a thickness of 5mm; the conductive beam 2 has parallel upper and lower sides, with an upper side length of 10mm, a lower side length of 160mm, and a thickness of 5mm; the polyester braided sleeve 3 has a length of 180mm, a width of 160mm, and an inner diameter of 5mm; the conical structure 7 has an upper base cross-sectional diameter of 5mm and a lower base cross-sectional diameter of 2mm; the elliptical composite rod 8 has a major axis length of 2.5mm and a minor axis length of 2.0mm; the single positioning element 9 has a cross-sectional length of 0.1mm and a width of 0.05mm. The thicknesses of brass layers I12, II22, and III52 are all 5µm; the thicknesses of lead-antimony-neodymium alloy layers I13, II23, and III53 are all 20µm; the thicknesses of lead-tin-bismuth alloy layers I14, II24, and III54 are all 0.5mm; and the thickness of the lead-tin composite plating 55 doped with nano-boron carbide / nano-cerium dioxide is 0.2mm. By mass percentage, the aluminum alloy contains 0.01% Ca, 0.5% Mn, 0.01% Ce, and 0.05% Zr, with the balance being Al; by mass percentage, the lead-antimony-neodymium alloy layer contains 0.5% Sb and 0.001% Nd, with the balance being Pb; by mass percentage, the lead-tin-bismuth alloy layer contains 0.5% Sn and 0.05% Bi, with the balance being Pb; by mass percentage, the lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide contains 1.0% B4C, 0.5% CeO2, and 0.5% Sn, with the balance being Pb. By mass percentage, the positive electrode active lead paste 6 contains 3.0% Pb3O4, 0.05% stannous sulfate, 0.10% graphite powder, 0.05% short fibers, 0.10% tetrabasic lead sulfate, 0.10% conductive fibers, 7.0% concentrated sulfuric acid, 5.0% H2O, 0.05% bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material, and the balance is lead-tin alloy powder containing 0.1 wt.% Sn; The preparation method of the bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI) in the positive electrode active lead paste specifically includes: 1) Zinc nitrate and bismuth nitrate are dissolved in anhydrous methanol solution to form a metal salt solution; the molar ratio of zinc nitrate to bismuth nitrate is 15:1; 2) Under vigorous stirring, a methanol ligand solution containing 2-methylimidazole was added dropwise to the metal salt solution. The reaction was stirred at room temperature for 24 hours to complete the self-assembly. After centrifugation, the mixture was washed multiple times with anhydrous ethanol and dried under vacuum to obtain the Bi-ZIF-8 precursor (MOF). The total molar ratio of zinc ions and bismuth ions in the metal salt solution to that of 2-methylimidazole (C4H6N2) was 1:8. 3) The Bi-ZIF-8 precursor was placed in a tube furnace and heated to 800℃ for 3 hours under an argon atmosphere at a heating rate of 5℃ / min. After cooling to room temperature in the furnace, excess elemental zinc was removed by washing with dilute hydrochloric acid to obtain bismuth-doped porous carbon (Bi-MOF-C) with a high specific surface area. The concentration of the dilute hydrochloric acid was 2 mol / L. 4) Bismuth-doped porous carbon (Bi-MOF-C) was uniformly dispersed in a 1 mol / L hydrochloric acid solution. Aniline monomer and ammonium persulfate (APS) initiator were added sequentially at 5 °C with stirring, and the reaction was carried out in situ for 12 h of oxidative polymerization. After washing with deionized water until neutral, the mixture was vacuum dried for 24 h to obtain a bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI). The mass ratio of bismuth-doped porous carbon (Bi-MOF-C) to aniline monomer was 1:3, and the molar ratio of aniline monomer to ammonium persulfate (APS) initiator was 1:1. The method for preparing the positive electrode grid of the tubular lead-carbon battery includes the following steps: S1. Preparation of aluminum alloy grid substrate: Molten aluminum alloy liquid is injected into a positive electrode grid mold for die casting (the die casting pressure is 50 bar), cooled, finely trimmed, and then subjected to degreasing and surface sandblasting treatments to obtain the aluminum alloy grid substrate; the aluminum alloy grid substrate includes aluminum alloy I for the tabs, aluminum alloy II for the conductive beams, and aluminum alloy III for the aluminum-based lead alloy composite rods; the preparation method of the molten aluminum alloy liquid is as follows: pure aluminum, Al-20%Mn master alloy, Al-5%Ce master alloy, and Al-5%Zr master alloy are added to a melting furnace, heated to 660℃ and held at that temperature to melt, and stirred by electromagnetic field for 5 minutes to obtain aluminum alloy melt, then a refining agent is added for refining, and after slag removal, the molten aluminum alloy liquid is obtained; by mass percentage, the refining agent contains 50% NaCl, 30% KCl, 15% MgCl2, and 5% hexachloroethane (C2Cl6); the refining agent accounts for 0.5 wt% of the aluminum alloy melt; S2. Preparation of the brass layer: The aluminum alloy grid substrate is immersed in a primary zinc plating solution for primary immersion plating. After rinsing with deionized water, it is activated in a 10% HNO3 solution for 1 second, and then immersed in a secondary zinc plating solution for secondary immersion plating. After rinsing with deionized water, a zinc@aluminum alloy substrate is obtained. Using the zinc@aluminum alloy substrate as the cathode and the Zn-Cu alloy (Zn accounting for 30 wt.%) as the anode, constant current electrodeposition is performed in a copper electroplating solution. After rinsing with deionized water and drying, an aluminum alloy grid substrate coated with a brass layer is obtained. The brass layer includes brass layer I, brass layer II, and brass layer III. The primary zinc plating solution contains 50 g / L Zn. The zinc plating solution contains 20 g / L ZnO, 100 g / L NaOH, 1 g / L FeCl3·6H2O, and 30 g / L potassium sodium tartrate; the first immersion plating temperature is 10℃ and the time is 30 s; the second zinc plating solution contains 20 g / L ZnO, 100 g / L NaOH, 1 g / L FeCl3·6H2O, 30 g / L potassium sodium tartrate, and 0.5 g / L NaNO3; the second immersion plating temperature is 10℃ and the time is 10 s; the copper plating solution contains 20 g / L copper pyrophosphate, 10 g / L zinc pyrophosphate, and 40 g / L potassium pyrophosphate, with a pH of 9.0; the cathode current density for constant current electrodeposition is 0.5 A / dm³. 2 The temperature was 50℃ and the time was 5 minutes. S3. Preparation of the lead-antimony-neodymium alloy layer: The aluminum alloy grid substrate coated with a brass layer is immersed in a flux activation solution for activation (immersion activation temperature is 100℃, immersion activation time is 10s), and then immersed in a lead-antimony-neodymium alloy melt for plating treatment (plating time is 20s), and immediately cooled in anhydrous ethanol to obtain an aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer; the lead-antimony-neodymium alloy layer includes lead-antimony-neodymium alloy layer I, lead-antimony-neodymium alloy layer II, and lead-antimony-neodymium alloy layer III; the flux activation solution contains 80wt% rosin, The composition includes 10 wt% n-butanol, 2 wt% succinic acid, 0.1 wt% fatty acid polyoxyethylene ether, 0.1 wt% hydroquinone, and 7.8 wt% anhydrous ethanol. The preparation method of the lead-antimony-neodymium alloy melt is as follows: pure lead, pure antimony, and lead-2% neodymium master alloy are added to a melting furnace, heated to 400℃ and held for melting, and stirred electromagnetically for 5 minutes to obtain molten lead alloy. Ammonium chloride powder is added as a purifying agent for stirring and purification. After settling and removing slag, the lead-antimony-neodymium alloy melt is obtained. The amount of ammonium chloride powder added is 0.5 wt% of the molten lead alloy. S4. Preparation of the lead-tin-bismuth alloy layer: An aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer and a brass layer is placed in a mold. Molten lead-tin-bismuth alloy is injected into the mold for die casting (the die casting pressure is 90 bar). After cooling and finishing, an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is obtained. The lead-tin-bismuth alloy layer includes lead-tin-bismuth alloy layer I, lead-tin-bismuth alloy layer II, and lead-tin-bismuth alloy layer III. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer I serves as an electrode tab, and the aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer II serves as a conductive beam. The method for preparing the molten lead-tin-bismuth alloy is as follows: Pure lead, pure tin, and pure bismuth are added to a melting furnace, heated to 300℃, held for melting, and stirred with an electromagnetic field for 5 minutes to obtain an alloy melt. Ammonium chloride powder is added as a purifying agent for stirring and purification. After settling and removing slag, the molten lead-tin-bismuth alloy is obtained. The amount of ammonium chloride powder added is 0.5 wt% of the alloy melt. S5. Preparation of lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide: The bottom of an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is inserted into the holes of a titanium strip to form an integral grid. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer III is used as the cathode, and a Pb-2%Sn alloy plate is used as the anode. Constant current electrodeposition is performed in an alkaline lead plating solution (the cathode current density for constant current electrodeposition is 0.5 A / dm²). 2 The process was carried out at 20°C for 1 hour, followed by washing with deionized water and drying. The titanium strip was then removed to obtain an aluminum alloy grid substrate coated with a lead-tin composite layer doped with nano-boron carbide / nano-cerium dioxide. The aluminum alloy grid substrate coated with the lead-tin composite layer doped with nano-boron carbide / nano-cerium dioxide was an aluminum-based lead alloy composite rod. The alkaline lead plating solution contained 10 g / L lead oxide, 10 g / L potassium hydroxide, 5 g / L potassium stannate, 30 g / L sodium potassium tartrate, 5 g / L nano-B4C, and 5 g / L nano-CeO2. S6. Insert the aluminum alloy grid substrate with a lead-tin composite coating of nano boron carbide / nano cerium dioxide into the polyester braided sleeve, then invert it so that the conductive beam is at the bottom, fill the gap between the aluminum-based lead alloy composite rod and the inner wall of the polyester braided sleeve with positive electrode active lead paste, seal the positive electrode active lead paste in the polyester braided sleeve with the sleeve plug, and suspend it for 24 hours to obtain the positive electrode grid of the tubular lead-carbon battery. In this embodiment, compared with conventional die-cast lead-calcium alloy grids, the positive grid of the tubular lead-carbon battery exhibits the following strength characteristics: Under room temperature conditions, a UTM4304SLXY electronic universal testing machine was used to tensile test both the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery positive grid at a tensile rate of 5 mm / min. The tensile results showed that the corresponding tensile strengths of the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery positive grid were 45.3 MPa and 54.8 MPa, respectively. The strength of the tubular lead-carbon battery positive grid is increased by 21.0% compared to the conventional die-cast lead-calcium alloy grid. Regarding cycle life: Under an ambient temperature of 25±2℃, a high-performance battery testing system from Xinwei was used to conduct a 100% DOD (depth of discharge) deep cycle life comparison test on the test batteries composed of the tubular lead-carbon battery positive grid and the conventional die-cast lead-calcium alloy grid. The specific test steps and cutoff conditions were set as follows: First, constant current discharge at a rate of 0.5C was applied until the single-cell termination voltage of 1.75V, followed by a resting period of 20 minutes; then constant current charging at a rate of 0.2C was applied until the single-cell constant voltage control point of 2.45V was reached, followed by constant voltage charging until the charging current naturally decayed to 0.02C, at which point charging was terminated, followed by a resting period of 20 minutes. This constitutes one complete charge-discharge cycle. Test results showed that the cycle life of the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery positive grid were 842 and 1106 cycles, respectively. Compared with the conventional die-cast lead-calcium alloy grid, the cycle life of the tubular lead-carbon battery positive grid in this embodiment was improved by 31.4%. Regarding charge acceptance capability (I... ca Regarding the method: After fully discharging the novel tubular lead-carbon battery and the conventional die-cast lead-calcium alloy battery, they were placed in an environment at 25±2℃ for at least 12 hours. Subsequently, at 25±2℃, the batteries were charged using the Xinwei high-performance battery testing system at a constant voltage of 2.45V per cell, and the charging current value at the 10th minute of charging was recorded. After testing and calculation, the charge acceptance capabilities of the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery's positive grid were 0.12A / Ah and 0.15A / Ah, respectively. Compared with the conventional die-cast lead-calcium alloy grid, the charge acceptance capability of the tubular lead-carbon battery's positive grid was improved by 25.0%.
[0031] Example 2: The positive grid structure of the tubular lead-carbon battery in this example is basically the same as that of the tubular lead-carbon battery in Example 1, except that: The electrode tab 1 is a cuboid structure with a height of 50mm, a width of 40mm, and a thickness of 10mm; the conductive beam 2 has parallel upper and lower sides, with an upper side length of 40mm, a lower side length of 480mm, and a thickness of 10mm; the polyester braided sleeve 3 has a length of 1000mm, a width of 480mm, and an inner diameter of 10mm; the conical structure 7 has an upper base cross-sectional diameter of 10mm and a lower base cross-sectional diameter of 6mm; the elliptical composite rod 8 has a major axis length of 7.0mm and a minor axis length of 5.0mm; the single positioning element 9 has a cross-sectional length of 1.0mm and a width of 0.5mm. The thicknesses of brass layers I12, II22, and III52 are all 30µm; the thicknesses of lead-antimony-neodymium alloy layers I13, II23, and III53 are all 100µm; the thicknesses of lead-tin-bismuth alloy layers I14, II24, and III54 are all 2.0mm; and the thickness of the lead-tin composite plating 55 doped with nano-boron carbide / nano-cerium dioxide is 1.0mm. By mass percentage, the aluminum alloy contains 0.5% Ca, 2.0% Mn, 0.1% Ce, and 1.2% Zr, with the balance being Al; by mass percentage, the lead-antimony-neodymium alloy layer contains 2.0% Sb and 0.2% Nd, with the balance being Pb; by mass percentage, the lead-tin-bismuth alloy layer contains 2.0% Sn and 0.5% Bi, with the balance being Pb; by mass percentage, the lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide contains 5.0% B4C, 2.0% CeO2, and 2.0% Sn, with the balance being Pb. By mass percentage, the positive electrode active lead paste 6 contains 10.0% Pb3O4, 0.2% stannous sulfate, 0.5% graphite powder, 0.15% short fibers, 0.40% tetrabasic lead sulfate, 0.50% conductive fibers, 11.0% concentrated sulfuric acid, 12.0% H2O, 0.5% bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material, and the balance is lead-tin alloy powder containing 0.1 wt.% Sn; The preparation method of the bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI) in the positive electrode active lead paste specifically includes: 1) Zinc nitrate and bismuth nitrate are dissolved in anhydrous methanol solution to form a metal salt solution; the molar ratio of zinc nitrate to bismuth nitrate is 9:1; 2) Under vigorous stirring, a methanol ligand solution containing 2-methylimidazole was added dropwise to the metal salt solution. The reaction was stirred at room temperature for 24 hours to complete the self-assembly. After centrifugation, the mixture was washed multiple times with anhydrous ethanol and dried under vacuum to obtain the Bi-ZIF-8 precursor (MOF). The total molar ratio of zinc ions and bismuth ions in the metal salt solution to that of 2-methylimidazole (C4H6N2) was 1:4. 3) The Bi-ZIF-8 precursor was placed in a tube furnace and heated to 1000℃ for high-temperature pyrolysis for 3 hours at a heating rate of 5℃ / min under an argon atmosphere. After cooling to room temperature in the furnace, excess elemental zinc was removed by washing with dilute hydrochloric acid to obtain bismuth-doped porous carbon (Bi-MOF-C) with a high specific surface area. The concentration of the dilute hydrochloric acid was 5 mol / L. 4) Bismuth-doped porous carbon (Bi-MOF-C) was uniformly dispersed in a 3 mol / L hydrochloric acid solution. Aniline monomer and ammonium persulfate (APS) initiator were added sequentially under stirring at 0 °C and in-situ oxidative polymerization was carried out for 12 h. After washing with deionized water until neutral, the mixture was vacuum dried for 26 h to obtain a bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI). The mass ratio of bismuth-doped porous carbon (Bi-MOF-C) to aniline monomer was 1:1, and the molar ratio of aniline monomer to ammonium persulfate (APS) initiator was 1:1. The method for preparing the positive electrode grid of the tubular lead-carbon battery includes the following steps: S1. Preparation of aluminum alloy grid substrate: Molten aluminum alloy liquid is injected into a positive electrode grid mold for die casting (the die casting pressure is 200 bar), cooled, finely trimmed, and then subjected to degreasing and surface sandblasting treatments to obtain the aluminum alloy grid substrate; the aluminum alloy grid substrate includes aluminum alloy I for the tabs, aluminum alloy II for the conductive beams, and aluminum alloy III for the aluminum-based lead alloy composite rods; the preparation method of the molten aluminum alloy liquid is as follows: pure aluminum, Al-20%Mn master alloy, Al-5%Ce master alloy, and Al-5%Zr master alloy are added to a melting furnace, heated to 720℃ and held at that temperature to melt, and stirred by electromagnetic field for 20 min to obtain aluminum alloy melt, then a refining agent is added for refining, and after slag removal, the molten aluminum alloy liquid is obtained; by mass percentage, the refining agent contains 25% NaCl, 40% KCl, 25% MgCl2, and 10% hexachloroethane (C2Cl6); the refining agent accounts for 2.0 wt% of the aluminum alloy melt; S2. Preparation of the brass layer: The aluminum alloy grid substrate is immersed in a primary zinc plating solution for primary immersion plating. After rinsing with deionized water, it is activated in a 40% HNO3 solution for 10 seconds, and then immersed in a secondary zinc plating solution for secondary immersion plating. After rinsing with deionized water, a zinc@aluminum alloy substrate is obtained. Using the zinc@aluminum alloy substrate as the cathode and the Zn-Cu alloy (Zn accounting for 30 wt.%) as the anode, constant current electrodeposition is performed in a copper electroplating solution. After rinsing with deionized water and drying, an aluminum alloy grid substrate coated with a brass layer is obtained. The brass layer includes brass layer I, brass layer II, and brass layer III. The primary zinc plating solution contains 70 g / The zinc plating solution contains 40 g / L ZnO, 200 g / L NaOH, 2 g / L FeCl3·6H2O, 60 g / L potassium sodium tartrate, and 2 g / L NaNO3; the first immersion plating temperature is 25℃ and the time is 60 s. The second immersion plating solution contains 40 g / L ZnO, 200 g / L NaOH, 2 g / L FeCl3·6H2O, 60 g / L potassium sodium tartrate, and 2 g / L NaNO3; the second immersion plating temperature is 25℃ and the time is 30 s. The copper plating solution contains 40 g / L copper pyrophosphate, 30 g / L zinc pyrophosphate, and 80 g / L potassium pyrophosphate, with a pH of 11.0. The cathode current density for constant current electrodeposition is 3 A / dm³. 2 The temperature was 70℃ and the time was 30 minutes. S3. Preparation of the lead-antimony-neodymium alloy layer: The aluminum alloy grid substrate coated with a brass layer is immersed in a flux activation solution for activation (immersion activation temperature is 200℃, immersion activation time is 60s), and then immersed in a lead-antimony-neodymium alloy melt for plating treatment (plating time is 120s), and immediately cooled in anhydrous ethanol to obtain an aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer; the lead-antimony-neodymium alloy layer includes lead-antimony-neodymium alloy layer I, lead-antimony-neodymium alloy layer II, and lead-antimony-neodymium alloy layer III; the flux activation solution contains 40wt% rosin, The composition includes 40 wt% n-butanol, 6 wt% succinic acid, 0.5 wt% fatty acid polyoxyethylene ether, 0.2 wt% hydroquinone, and 13.3 wt% anhydrous ethanol. The preparation method of the lead-antimony-neodymium alloy melt is as follows: pure lead, pure antimony, and lead-2% neodymium master alloy are added to a melting furnace, heated to 600℃ and held for melting, and stirred electromagnetically for 20 minutes to obtain molten lead alloy. Ammonium chloride powder is added as a purifying agent for stirring and purification. After settling and removing slag, the lead-antimony-neodymium alloy melt is obtained. The amount of ammonium chloride powder added is 2 wt% of the molten lead alloy. S4. Preparation of the lead-tin-bismuth alloy layer: An aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer and a brass layer is placed in a mold. Molten lead-tin-bismuth alloy is injected into the mold for die casting (the die casting pressure is 180 bar). After cooling and finishing, an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is obtained. The lead-tin-bismuth alloy layer includes lead-tin-bismuth alloy layer I, lead-tin-bismuth alloy layer II, and lead-tin-bismuth alloy layer III. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer I serves as an electrode tab, and the aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer II serves as a conductive beam. The method for preparing the molten lead-tin-bismuth alloy is as follows: Pure lead, pure tin, and pure bismuth are added to a melting furnace, heated to 400℃, held for melting, and stirred with an electromagnetic field for 20 minutes to obtain an alloy melt. Ammonium chloride powder is added as a purifying agent for stirring and purification. After settling and removing slag, the molten lead-tin-bismuth alloy is obtained. The amount of ammonium chloride powder added is 2.0 wt% of the alloy melt. S5. Preparation of lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide: The bottom of an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is inserted into the holes of a titanium strip to form an integral grid. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer III is used as the cathode, and a Pb-2%Sn alloy plate is used as the anode. Constant current electrodeposition is performed in an alkaline lead plating solution (the cathode current density for constant current electrodeposition is 3 A / dm³). 2 The process was carried out at 50°C for 6 hours. After washing with deionized water and drying, the titanium strip was removed to obtain an aluminum alloy grid substrate coated with a lead-tin composite layer doped with nano-boron carbide / nano-cerium dioxide. The aluminum alloy grid substrate coated with the lead-tin composite layer doped with nano-boron carbide / nano-cerium dioxide was an aluminum-based lead alloy composite rod. The alkaline lead plating solution contained 50 g / L lead oxide, 30 g / L potassium hydroxide, 20 g / L potassium stannate, 80 g / L sodium potassium tartrate, 20 g / L nano-B4C, and 20 g / L nano-CeO2. S6. Insert the aluminum alloy grid substrate with a lead-tin composite coating of nano boron carbide / nano cerium dioxide into a polyester braided sleeve, then invert it so that the conductive beam is at the bottom, fill the gap between the aluminum-based lead alloy composite rod and the inner wall of the polyester braided sleeve with positive electrode active lead paste, seal the positive electrode active lead paste in the polyester braided sleeve with a sleeve plug, and suspend it for 48 hours to obtain the positive electrode grid of the tubular lead-carbon battery. In this embodiment, compared with conventional die-cast lead-calcium alloy grids, the positive grid of the tubular lead-carbon battery exhibits the following strength characteristics: Under room temperature conditions, a UTM4304SLXY electronic universal testing machine was used to tensile test both the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery positive grid at a tensile rate of 5 mm / min. The tensile results showed that the corresponding tensile strengths of the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery positive grid were 45.3 MPa and 56.2 MPa, respectively. The strength of the tubular lead-carbon battery positive grid is increased by 24.1% compared to the conventional die-cast lead-calcium alloy grid. Regarding cycle life: Under an ambient temperature of 25±2℃, a high-performance battery testing system from Xinwei was used to conduct a 100% DOD (depth of discharge) deep cycle life comparison test on the test batteries composed of the tubular lead-carbon battery positive grid and the conventional die-cast lead-calcium alloy grid. The specific test steps and cutoff conditions were set as follows: First, constant current discharge at a rate of 0.5C was applied until the single-cell termination voltage of 1.75V, followed by a resting period of 20 minutes; then constant current charging at a rate of 0.2C was applied until the single-cell constant voltage control point of 2.45V was reached, followed by constant voltage charging until the charging current naturally decayed to 0.02C, at which point charging was terminated, followed by a resting period of 20 minutes. This constitutes one complete charge-discharge cycle. Test results showed that the cycle life of the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery positive grid were 842 and 1168 cycles, respectively. Compared with the conventional die-cast lead-calcium alloy grid, the cycle life of the tubular lead-carbon battery positive grid in this embodiment was improved by 38.7%. Regarding charge acceptance capability (I... ca Regarding the method: After fully discharging the novel tubular lead-carbon battery and a conventional die-cast lead-calcium alloy battery, they were placed in an environment at 25±2℃ for at least 12 hours. Subsequently, at 25±2℃, the batteries were charged using a high-performance battery testing system from Xinwei at a constant voltage of 2.45V per cell, and the charging current value at the 10th minute of charging was recorded. After testing and calculation, the charge acceptance capabilities of the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery's positive grid were 0.12A / Ah and 0.16A / Ah, respectively. Compared with the conventional die-cast lead-calcium alloy grid, the charge acceptance capability of the tubular lead-carbon battery's positive grid was improved by 33.3%.
[0032] Example 3: The positive grid structure of the tubular lead-carbon battery in this example is basically the same as that of the tubular lead-carbon battery in Example 1, except that: The electrode tab 1 is a cuboid structure with a height of 35mm, a width of 25mm, and a thickness of 7mm; the conductive beam 2 has parallel upper and lower sides, with an upper side length of 25mm, a lower side length of 320mm, and a thickness of 7mm; the polyester braided sleeve 3 has a length of 590mm, a width of 320mm, and an inner diameter of 7mm; the conical structure 7 has an upper base cross-sectional diameter of 7mm and a lower base cross-sectional diameter of 4mm; the elliptical composite rod 8 has a major axis length of 5mm and a minor axis length of 3.5mm; the single positioning element 9 has a cross-sectional length of 0.5mm and a width of 0.25mm. The thicknesses of brass layers I12, II22, and III52 are all 17µm; the thicknesses of lead-antimony-neodymium alloy layers I13, II23, and III53 are all 60µm; the thicknesses of lead-tin-bismuth alloy layers I14, II24, and III54 are all 1.2mm; and the thickness of the lead-tin composite plating 55 doped with nano-boron carbide / nano-cerium dioxide is 0.6mm. By mass percentage, the aluminum alloy contains 0.25% Ca, 1.2% Mn, 0.05% Ce, and 0.6% Zr, with the balance being Al; by mass percentage, the lead-antimony-neodymium alloy layer contains 1.2% Sb and 0.1% Nd, with the balance being Pb; by mass percentage, the lead-tin-bismuth alloy layer contains 1.2% Sn and 0.25% Bi, with the balance being Pb; by mass percentage, the lead-tin composite plating layer 55 doped with nano-boron carbide / nano-cerium dioxide contains 3.0% B4C, 1.2% CeO2, and 1.2% Sn, with the balance being Pb. By mass percentage, the positive electrode active lead paste 6 contains 6.5% Pb3O4, 0.12% stannous sulfate, 0.30% graphite powder, 0.10% short fibers, 0.25% tetrabasic lead sulfate, 0.40% conductive fibers, 9.0% concentrated sulfuric acid, 8.5% H2O, 0.30% bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material, and the balance is lead-tin alloy powder containing 0.1 wt.% Sn; The preparation method of the bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI) in the positive electrode active lead paste specifically includes: 1) Zinc nitrate and bismuth nitrate are dissolved in anhydrous methanol solution to form a metal salt solution; the molar ratio of zinc nitrate to bismuth nitrate is 12:1; 2) Under vigorous stirring, a methanol ligand solution containing 2-methylimidazole was added dropwise to the metal salt solution. The reaction was stirred at room temperature for 24 h to complete the self-assembly. After centrifugation, the mixture was washed multiple times with anhydrous ethanol and dried under vacuum to obtain the Bi-ZIF-8 precursor (MOF). The total molar ratio of zinc ions and bismuth ions in the metal salt solution to that of 2-methylimidazole (C4H6N2) was 1:6. 3) The Bi-ZIF-8 precursor was placed in a tube furnace and heated to 900℃ for high-temperature pyrolysis for 3 hours at a heating rate of 5℃ / min under a nitrogen atmosphere. After cooling to room temperature in the furnace, excess elemental zinc was removed by washing with dilute hydrochloric acid to obtain bismuth-doped porous carbon (Bi-MOF-C) with a high specific surface area. The concentration of the dilute hydrochloric acid was 4 mol / L. 4) Bismuth-doped porous carbon (Bi-MOF-C) was uniformly dispersed in a 2 mol / L hydrochloric acid solution. Aniline monomer and ammonium persulfate (APS) initiator were added sequentially under stirring at 0 °C and in situ oxidative polymerization was carried out for 12 h. After washing with deionized water until neutral, the mixture was vacuum dried for 26 h to obtain a bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material (Bi-MOF-C@PANI). The mass ratio of bismuth-doped porous carbon (Bi-MOF-C) to aniline monomer was 1:2, and the molar ratio of aniline monomer to ammonium persulfate (APS) initiator was 1:2. The method for preparing the positive electrode grid of the tubular lead-carbon battery includes the following steps: S1. Preparation of aluminum alloy grid substrate: Molten aluminum alloy liquid is injected into a positive electrode grid mold for die casting (the die casting pressure is 125 bar), cooled, finely trimmed, and then subjected to degreasing and surface sandblasting treatments to obtain the aluminum alloy grid substrate; the aluminum alloy grid substrate includes aluminum alloy I for the tabs, aluminum alloy II for the conductive beams, and aluminum alloy III for the aluminum-based lead alloy composite rods; the preparation method of the molten aluminum alloy liquid is as follows: pure aluminum, Al-20%Mn master alloy, Al-5%Ce master alloy, and Al-5%Zr master alloy are added to a melting furnace, heated to 690℃ and held at that temperature to melt, and stirred by electromagnetic field for 12 minutes to obtain aluminum alloy melt, then a refining agent is added for refining, and after slag removal, the molten aluminum alloy liquid is obtained; by mass percentage, the refining agent contains 38% NaCl, 35% KCl, 20% MgCl2, and 7% hexachloroethane (C2Cl6); the refining agent accounts for 1.2 wt% of the aluminum alloy melt; S2. Preparation of the brass layer: The aluminum alloy grid substrate is immersed in a primary zinc plating solution for primary immersion plating. After rinsing with deionized water, it is activated in a 25% HNO3 solution for 5 seconds, and then immersed in a secondary zinc plating solution for secondary immersion plating. After rinsing with deionized water, a zinc@aluminum alloy substrate is obtained. Using the zinc@aluminum alloy substrate as the cathode and a Zn-Cu alloy (Zn accounting for 30 wt.%) as the anode, constant current electrodeposition is performed in a copper electroplating solution. After rinsing with deionized water and drying, an aluminum alloy grid substrate coated with a brass layer is obtained. The brass layer includes brass layer I, brass layer II, and brass layer III. The primary zinc plating solution contains 60 g / L ZnO. The zinc plating solution contained 300 g / L NaOH, 1.5 g / L FeCl3·6H2O, and 20 g / L potassium sodium tartrate; the first immersion plating temperature was 17℃ and the time was 45 s; the second zinc plating solution contained 30 g / L ZnO, 150 g / L NaOH, 1.5 g / L FeCl3·6H2O, 45 g / L potassium sodium tartrate, and 1.2 g / L NaNO3; the second immersion plating temperature was 17℃ and the time was 20 s; the copper plating solution contained 30 g / L copper pyrophosphate, 20 g / L zinc pyrophosphate, and 60 g / L potassium pyrophosphate, with a pH of 10.0; the cathode current density for constant current electrodeposition was 1.75 A / dm³. 2 The temperature was 60℃ and the time was 17 minutes. S3. Preparation of the lead-antimony-neodymium alloy layer: The aluminum alloy grid substrate coated with a brass layer is immersed in a flux activation solution for activation (immersion activation temperature is 150℃, immersion activation time is 35s), and then immersed in a lead-antimony-neodymium alloy melt for plating treatment (plating time is 120s), and immediately cooled in anhydrous ethanol to obtain an aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer; the lead-antimony-neodymium alloy layer includes lead-antimony-neodymium alloy layer I, lead-antimony-neodymium alloy layer II, and lead-antimony-neodymium alloy layer III; the flux activation solution contains 60wt% rosin and 25%... The composition includes wt% n-butanol, 4wt% succinic acid, 0.3wt% fatty acid polyoxyethylene ether, 0.15wt% hydroquinone, and 10.55wt% anhydrous ethanol. The preparation method of the lead-antimony-neodymium alloy melt is as follows: pure lead, pure antimony, and lead-2% neodymium master alloy are added to a melting furnace, heated to 500℃ and held for melting, and stirred electromagnetically for 10 minutes to obtain molten lead alloy. Ammonium chloride powder is added as a purifying agent for stirring and purification. After settling and removing slag, the lead-antimony-neodymium alloy melt is obtained. The amount of ammonium chloride powder added is 1.2wt% of the molten lead alloy. S4. Preparation of the lead-tin-bismuth alloy layer: An aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer and a brass layer is placed in a mold. Molten lead-tin-bismuth alloy is injected into the mold for die casting (the die casting pressure is 135 bar). After cooling and finishing, an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is obtained. The lead-tin-bismuth alloy layer includes lead-tin-bismuth alloy layer I, lead-tin-bismuth alloy layer II, and lead-tin-bismuth alloy layer III. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer I serves as an electrode tab, and the aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer II serves as a conductive beam. The method for preparing the molten lead-tin-bismuth alloy is as follows: Pure lead, pure tin, and pure bismuth are added to a melting furnace, heated to 350℃, held for melting, and stirred with an electromagnetic field for 12 minutes to obtain an alloy melt. Ammonium chloride powder is added as a purifying agent for stirring and purification. After settling and removing slag, the molten lead-tin-bismuth alloy is obtained. The amount of ammonium chloride powder added is 1.2 wt% of the alloy melt. S5. Preparation of lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide: The bottom of an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is inserted into the holes of a titanium strip to form an integral grid. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer III is used as the cathode, and a Pb-2%Sn alloy plate is used as the anode. Constant current electrodeposition is performed in an alkaline lead plating solution (the cathode current density for constant current electrodeposition is 1.75 A / dm²). 2 The process was carried out at 35°C for 3.5 hours. After washing with deionized water and drying, the titanium strip was removed to obtain an aluminum alloy grid substrate coated with a lead-tin composite layer doped with nano-boron carbide / nano-cerium dioxide. The aluminum alloy grid substrate coated with the lead-tin composite layer doped with nano-boron carbide / nano-cerium dioxide was an aluminum-based lead alloy composite rod. The alkaline lead plating solution contained 30 g / L lead oxide, 20 g / L potassium hydroxide, 12 g / L potassium stannate, 55 g / L potassium sodium tartrate, 12 g / L nano B4C, and 12 g / L nano CeO2. S6. Insert the aluminum alloy grid substrate with a lead-tin composite coating of nano boron carbide / nano cerium dioxide into a polyester braided sleeve, then invert it so that the conductive beam is at the bottom, fill the gap between the aluminum-based lead alloy composite rod and the inner wall of the polyester braided sleeve with positive electrode active lead paste, seal the positive electrode active lead paste in the polyester braided sleeve with a sleeve plug, and suspend it for 36 hours to obtain the positive electrode grid of the tubular lead-carbon battery. In this embodiment, compared with conventional die-cast lead-calcium alloy grids, the positive grid of the tubular lead-carbon battery exhibits the following strength characteristics: Under room temperature conditions, a UTM4304SLXY electronic universal testing machine was used to tensile test both the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery positive grid at a tensile rate of 5 mm / min. The tensile results showed that the corresponding tensile strengths of the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery positive grid were 45.3 MPa and 58.7 MPa, respectively. The strength of the tubular lead-carbon battery positive grid is increased by 29.6% compared to the conventional die-cast lead-calcium alloy grid. Regarding cycle life: Under an ambient temperature of 25±2℃, a high-performance battery testing system from Xinwei was used to conduct a 100% DOD (depth of discharge) deep cycle life comparison test on the test batteries composed of the tubular lead-carbon battery positive grid and the conventional die-cast lead-calcium alloy grid. The specific test steps and cutoff conditions were set as follows: First, constant current discharge at a rate of 0.5C was applied until the single-cell termination voltage of 1.75V was reached, followed by a resting period of 20 minutes; then, constant current charging at a rate of 0.2C was applied until the single-cell constant voltage control point of 2.45V was reached, followed by constant voltage charging until the charging current naturally decayed to 0.02C, at which point charging was terminated, followed by a resting period of 20 minutes. This constitutes one complete charge-discharge cycle. Test results showed that the cycle life of the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery positive grid were 842 and 1225 cycles, respectively. Compared with the conventional die-cast lead-calcium alloy grid, the cycle life of the tubular lead-carbon battery positive grid in this embodiment was improved by 45.5%. Regarding charge acceptance capability (I... ca Regarding the method: After fully discharging the novel tubular lead-carbon battery and the conventional die-cast lead-calcium alloy battery, they were placed in an environment at 25±2℃ for at least 12 hours. Subsequently, at 25±2℃, the batteries were charged using the Xinwei high-performance battery testing system at a constant voltage of 2.45V per cell, and the charging current value at the 10th minute of charging was recorded. After testing and calculation, the charge acceptance capabilities of the conventional die-cast lead-calcium alloy grid and the tubular lead-carbon battery's positive grid were 0.12A / Ah and 0.18A / Ah, respectively. Compared with the conventional die-cast lead-calcium alloy grid, the charge acceptance capability of the tubular lead-carbon battery's positive grid was improved by 50.0%.
[0033] The specific embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.
Claims
1. A positive electrode grid for a tubular lead-carbon battery, characterized in that: The device includes an electrode tab (1), a conductive beam (2), a polyester braided sleeve (3), a sleeve plug (4), and an aluminum-based lead alloy composite rod (5). The electrode tab (1) is set at the top of the conductive beam (2), and the aluminum-based lead alloy composite rod (5) is set vertically at equal intervals at the bottom of the conductive beam (2). The polyester braided sleeve (3) is sleeved on the outside of the aluminum-based lead alloy composite rod (5), and the gap between the aluminum-based lead alloy composite rod (5) and the inner wall of the polyester braided sleeve (3) is filled with positive electrode active lead paste (6). The sleeve plug (4) is set at the bottom of the polyester braided sleeve (3). Several pairs of positioning parts (9) are set on the side of the aluminum-based lead alloy composite rod (5) along the axial direction. The top of the aluminum-based lead alloy composite rod (5) is a conical structure (7), and the bottom of the conical structure (7) is an integrally formed elliptical composite rod structure (8). The electrode (1) consists of aluminum alloy I (11), brass layer I (12), lead-antimony-neodymium alloy layer I (13) and lead-tin-bismuth alloy layer I (14) from the inside to the outside. The conductive crossbeam (2) consists of aluminum alloy II (21), brass layer II (22), lead-antimony-neodymium alloy layer II (23) and lead-tin-bismuth alloy layer II (24) from the inside to the outside. The aluminum-based lead alloy composite rod (5) consists of, from the inside out, aluminum alloy III (51), brass layer III (52), lead-antimony-neodymium alloy layer III (53), lead-tin-bismuth alloy layer III (54), and lead-tin composite plating layer (55) doped with nano boron carbide / nano cerium dioxide.
2. The positive grid of the tubular lead-carbon battery according to claim 1, characterized in that: The positioning element (9) includes positioning element I (91) and positioning element II (92). Positioning element I (91) and positioning element II (92) are alternately arranged along the axial direction on the outside of the elliptical composite rod structure (8). Each pair of positioning elements I (91) is arranged along the major axis of the elliptical composite rod structure (8) and is symmetrical with respect to the central axis of the aluminum-based lead alloy composite rod (5). Each pair of positioning elements II (92) is arranged along the minor axis of the elliptical composite rod structure (8) and is symmetrical with respect to the central axis of the aluminum-based lead alloy composite rod (5). The spacing between adjacent pairs of positioning elements I (91) is equal, and the spacing between adjacent pairs of positioning elements II (92) is equal.
3. The positive grid of the tubular lead-carbon battery according to claim 2, characterized in that: The electrode tab (1) is a cuboid structure with a height of 20-50 mm, a width of 10-40 mm, and a thickness of 5-10 mm; the conductive beam (2) has parallel upper and lower sides, with an upper side length of 10-40 mm, a lower side length of 160-480 mm, and a thickness of 5-10 mm; the polyester braided sleeve (3) has a length of 180-1000 mm, a width of 160-480 mm, and an inner diameter of 5-10 mm; the cone structure (7) has an upper base cross-section diameter of 5-10 mm and a lower base cross-section diameter of 2-6 mm; the elliptical composite rod (8) has a major axis length of 2.5-7.0 mm and a minor axis length of 2.0-5.0 mm; the single positioning element (9) has a cross-sectional length of 0.1-1.0 mm and a width of 0.05-0.5 mm.
4. The positive grid of the tubular lead-carbon battery according to claim 1, characterized in that: The thickness of brass layer I (12) is 5~30µm, and the thicknesses of brass layer I (12), brass layer II (22) and brass layer III (52) are the same; the thickness of lead-antimony-neodymium alloy layer I (13) is 20~100µm, and the thicknesses of lead-antimony-neodymium alloy layer I (13), lead-antimony-neodymium alloy layer II (23) and lead-antimony-neodymium alloy layer III (53) are the same; the thickness of lead-tin-bismuth alloy layer I (14) is 0.5~2.0mm, and the thicknesses of lead-tin-bismuth alloy layer I (14), lead-tin-bismuth alloy layer II (24) and lead-tin-bismuth alloy layer III (54) are the same; the thickness of lead-tin composite plating layer (55) doped with nano boron carbide / nano cerium dioxide is 0.2~1.0mm.
5. The positive grid of the tubular lead-carbon battery according to claim 1, characterized in that: By mass percentage, the aluminum alloy contains 0.01~0.5% Ca, 0.5~2.0% Mn, 0.01~0.1% Ce, 0.05~1.2% Zr, with the balance being Al; by mass percentage, the lead-antimony-neodymium alloy layer contains 0.5~2.0% Sb, 0.001~0.2% Nd, with the balance being Pb; by mass percentage, the lead-tin-bismuth alloy layer contains 0.5~2.0% Sn, 0.05~0.5% Bi, with the balance being Pb; by mass percentage, the lead-tin composite plating layer (55) doped with nano-boron carbide / nano-cerium dioxide contains 1.0~5.0% B4C, 0.5~2.0% CeO2, 0.5~2.0% Sn, with the balance being Pb.
6. The positive grid of the tubular lead-carbon battery according to claim 1, characterized in that: The positive electrode active lead paste (6) contains, by mass percentage, 3.0-10.0% Pb3O4, 0.05-0.20% stannous sulfate, 0.10-0.50% graphite powder, 0.05-0.15% short fibers, 0.10-0.40% tetrabasic lead sulfate, 0.10-0.50% conductive fibers, 7.0-11.0% concentrated sulfuric acid, 5.0-12.0% H2O, 0.05-0.50% bismuth-doped MOF-derived porous carbon-supported conductive polymer composite material, and the balance being lead-tin alloy powder containing 0.1 wt.% Sn.
7. The method for preparing the positive grid of the tubular lead-carbon battery according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Preparation of aluminum alloy grid substrate: Molten aluminum alloy liquid is injected into a positive electrode grid mold for die casting, cooled, and finely repaired. Then, it is subjected to degreasing and surface sandblasting treatment in sequence to obtain aluminum alloy grid substrate; the aluminum alloy grid substrate includes aluminum alloy I for the tabs, aluminum alloy II for the conductive beams, and aluminum alloy III for the aluminum-based lead alloy composite rods. S2. Preparation of the brass layer: The aluminum alloy grid substrate is immersed in a primary zinc plating solution for primary immersion plating. After cleaning with deionized water, it is activated in an HNO3 solution and then immersed in a secondary zinc plating solution for secondary immersion plating. After cleaning with deionized water, a zinc@aluminum alloy substrate is obtained. Using the zinc@aluminum alloy substrate as the cathode and the Zn-Cu alloy as the anode, constant current electrodeposition is performed in a copper electroplating solution. After cleaning with deionized water and drying, an aluminum alloy grid substrate coated with a brass layer is obtained. The brass layer includes brass layer I, brass layer II, and brass layer III. S3. Preparation of lead-antimony-neodymium alloy layer: The aluminum alloy grid substrate coated with brass layer is immersed in flux activation solution for activation, then immersed in lead-antimony-neodymium alloy melt for plating treatment, and immediately cooled in anhydrous ethanol to obtain an aluminum alloy grid substrate coated with lead-antimony-neodymium alloy layer; the lead-antimony-neodymium alloy layer includes lead-antimony-neodymium alloy layer I, lead-antimony-neodymium alloy layer II and lead-antimony-neodymium alloy layer III; S4. Preparation of lead-tin-bismuth alloy layer: An aluminum alloy grid substrate coated with a lead-antimony-neodymium alloy layer and a brass layer is placed in a mold, and molten lead-tin-bismuth alloy is injected into the mold for die casting. After cooling and finishing, an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is obtained. The lead-tin-bismuth alloy layer includes lead-tin-bismuth alloy layer I, lead-tin-bismuth alloy layer II, and lead-tin-bismuth alloy layer III. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer I is the electrode tab, and the aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer II is the conductive beam. S5. Preparation of lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide: The bottom of an aluminum alloy grid substrate coated with a lead-tin-bismuth alloy layer is inserted into the hole of a titanium strip to form an integral grid. The aluminum alloy grid substrate coated with lead-tin-bismuth alloy layer III is used as the cathode, and the Pb-2%Sn alloy plate is used as the anode. Constant current electrodeposition is performed in an alkaline lead plating solution. After washing with deionized water and drying, the titanium strip is removed to obtain an aluminum alloy grid substrate coated with a lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide. The aluminum alloy grid substrate coated with the lead-tin composite coating doped with nano-boron carbide / nano-cerium dioxide is an aluminum-based lead alloy composite rod. S6. Insert the aluminum alloy grid substrate with a lead-tin composite coating of nano-boron carbide / nano-cerium dioxide into a polyester braided sleeve, then invert it so that the conductive beam is at the bottom, fill the gap between the aluminum-based lead alloy composite rod and the inner wall of the polyester braided sleeve with positive electrode active lead paste, seal the positive electrode active lead paste in the polyester braided sleeve with a sleeve plug, and suspend it for 24~48 hours to obtain the positive electrode grid of the tubular lead-carbon battery.
8. The method for preparing the positive grid of the tubular lead-carbon battery according to claim 7, characterized in that: Step S1 Preparation method of molten aluminum alloy liquid: Pure aluminum, Al-20%Mn master alloy, Al-5%Ce master alloy, and Al-5%Zr master alloy are added into a melting furnace, heated to 660~720℃ and held to melt, and stirred by electromagnetic field for 5~20 minutes to obtain aluminum alloy melt. Then, a refining agent is added for refining, and after slag removal, molten aluminum alloy liquid is obtained. Step S3 Preparation method of lead-antimony-neodymium alloy melt: Pure lead, pure antimony and lead-2% neodymium master alloy are added into a melting furnace, heated to 400~600℃ and held for melting, and stirred in an electromagnetic field for 5~20 minutes to obtain molten lead alloy. Ammonium chloride powder is added as a purifying agent and stirred for purification. After standing and removing slag, lead-antimony-neodymium alloy melt is obtained. Step S4 Preparation method of lead-tin-bismuth alloy melt: Add pure lead, pure tin and pure bismuth into a melting furnace, heat to 300~400℃ and hold for melting, and stir with an electromagnetic field for 5~20 minutes to obtain alloy melt. Add ammonium chloride powder as a purifying agent and stir for purification. Let stand and remove slag to obtain lead-tin-bismuth alloy melt.
9. The method for preparing the positive grid of the tubular lead-carbon battery according to claim 7, characterized in that: Step S2: The primary zinc plating solution contains 50-70 g / L ZnO, 250-350 g / L NaOH, 1-2 g / L FeCl3·6H2O, and 10-30 g / L potassium sodium tartrate; the secondary zinc plating solution contains 20-40 g / L ZnO, 100-200 g / L NaOH, 1-2 g / L FeCl3·6H2O, 30-60 g / L potassium sodium tartrate, and 0.5-2 g / L NaNO3. The copper electroplating solution in step S2 contains 20-40 g / L copper pyrophosphate, 10-30 g / L zinc pyrophosphate, and 40-80 g / L potassium pyrophosphate, with a pH value of 9.0-11.
0. The flux activating solution in step S3 contains 40-80 wt% rosin, 10-40 wt% n-butanol, 2-6 wt% succinic acid, 0.1-0.5 wt% fatty acid polyoxyethylene ether, 0.1-0.2 wt% hydroquinone and 7.8-13.3 wt% anhydrous ethanol; The alkaline lead plating solution in step S5 contains 10~50g / L lead oxide, 10~30g / L potassium hydroxide, 5~20g / L potassium stannate, 30~80g / L sodium potassium tartrate, 5~20g / L nano B4C, and 5~20g / L nano CeO2.
10. The method for preparing the positive electrode grid of the tubular lead-carbon battery according to claim 7, characterized in that: The pressure for die casting in step S1 is 50~200 bar; In step S2, the temperature for the first immersion plating is 10~25℃, and the time is 30~60s; the temperature for the second immersion plating is 10~25℃, and the time is 10~30s; the cathode current density for constant current electrodeposition is 0.5~3A / dm³. 2 The temperature is 50~70℃, and the time is 5~30min; The immersion activation temperature in step S3 is 100~200℃, and the immersion activation time is 10~60S; the immersion plating time is 20~120S. The pressure for die casting in step S4 is 90~180 bar; In step S5, the cathode current density for constant current electrodeposition is 0.5~3 A / dm³. 2 The temperature is 20~50℃, and the time is 1~6h.
Citation Information
Patent Citations
Anode plate for netting tube type seal lead power batteries
CN202487700U